Design and Characterization of Biomimetic Hybrid Construct Based on Hyaluronic Acid and Alginate Bioink for Regeneration of Articular Cartilage - Cristina Galocha-León; Cristina Antich; Beatriz Clares-Naveros; Ana Voltes-Martínez; Juan Antonio Marchal; Patricia Gálvez-Martín (Pharmaceutics)
Background/Objectives: Three-dimensional bioprinting technology has enabled great advances in the treatment of articular cartilage (AC) defects by the biofabrication of biomimetic constructs that restore and/or regenerate damaged tissue. In this sense, the selection of suitable cells and biomaterials to bioprint constructs that mimic the architecture, composition, and functionality of the natural extracellular matrix (ECM) of the native tissue is crucial. In the present study, a novel cartilage-like biomimetic hybrid construct (CBC) was developed by 3D bioprinting to facilitate and promote AC regeneration. Methods: The CBC was biofabricated by the co-bioprinting of a bioink based on hyaluronic acid (HA) and alginate (AL) loaded with human mesenchymal stromal cells (hMSCs), with polylactic acid supporting the biomaterial, in order to mimic the microenvironment and structural properties of native AC, respectively. The CBC was biologically in vitro characterized. In addition, its physiochemical characteristics were evaluated in order to determine if the presence of hMSCs modified its properties. Results: Results from biological analysis demonstrated that CBC supported the high viability and proliferation of hMSCs, facilitating chondrogenesis after 5 weeks in vitro. The evaluation of physicochemical properties in the CBCs confirmed that the CBC developed could be suitable for use in cartilage tissue engineering. Conclusions: The results demonstrated that the use of bioprinted CBCs based on hMSC-AL/HA-bioink for AC repair could enhance the regeneration and/or formation of hyaline cartilaginous tissue.